2023
DOI: 10.1016/j.lanwpc.2022.100390
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care system responses to non-communicable disease prevention and control: a scoping review of national policies in Mainland China since the 2009 health reform

Abstract: This study aims to review China's national policies related to non-communicable disease (NCD) prevention and control at the primary health care (PHC) level since China's 2009 health system reform. Policy documents from official websites of China's State Council and 20 affiliated ministries were screened, where 151 out of 1,799 were included. Thematic content analysis was performed, and fourteen 'major policy initiatives' were identified, including the basic health insurance schemes and essential public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Life habits generally affect hypertension, one of which is obesity or overeating (Kane et al, 2012). Although the mechanism of how obesity affects hypertension is not yet apparent, it has been evident that weight loss can lower blood pressure (Xiong et al, 2022). A highcalorie diet, fatty, smoking and drinking alcohol are one of the behaviors causing several diseases, encompassing hypertension (Parashar et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Life habits generally affect hypertension, one of which is obesity or overeating (Kane et al, 2012). Although the mechanism of how obesity affects hypertension is not yet apparent, it has been evident that weight loss can lower blood pressure (Xiong et al, 2022). A highcalorie diet, fatty, smoking and drinking alcohol are one of the behaviors causing several diseases, encompassing hypertension (Parashar et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…This finding aligns with a previously published scoping review of China's national policies on PHC strengthening and NCD control, where researchers found that despite the rhetoric of advocating for cross-sectorial collaboration, policy documents seldom provided concrete action plans to facilitate and evaluate multi-sectorial involvement in PHC affairs. 15 “Health in all policies” approaches have been shown in several country case studies to be a determinant for successful PHC strengthening in many low-and middle-income countries (LMICs). 16 This requires sustained political commitment and leadership to integration health into policymaking across all government sectors.…”
Section: Discussionmentioning
confidence: 99%
“…16 This requires sustained political commitment and leadership to integration health into policymaking across all government sectors. 17 Given the hierarchical nature of China's policy-making processes, 15 , 18 a “health in all policies” strategy for cross-sectorial engagement will likely require mandated regulations. For example, future modifications to NEPHSP standards could explore the assignment of health education responsibilities – a part of NEPHSP – to both the health and education sectors, with specified roles, obligations, and incentives.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mental health assessment or dietary patterns may not be collected routinely. It might be necessary to establish an integrated health information system of integrating the existing routinely collected data systems, 99 maximising the use of such data, to comprehensively and timely understand the burden of multimorbidity.…”
Section: Discussionmentioning
confidence: 99%